The professional social educator in the daily life of adolescents of reception unit: an integrative review (Research, Society and Development, 2021)
This study aimed to analyze the role of social educators with adolescents in institutional reception units. Qualitative, descriptive integrative research, carried out in the Virtual Health Library, with publications of the last decade, associating the Keys Word and the descriptors in health: shelter; social educator; educators and host unit. The results pointed out the relevance of the role of social educators today. The profile of educators is mostly female; are generally between 20 and 66 years of age and with high school education. They exercise non-formal education that proposes the development of the social being, developed in groups at social risk in the context of the host units, not always obtaining specific training for action. They establish care, based on their own personal experience. It is considered that this profession favors the emancipation and transformation of subjects who are in a situation of risk and social vulnerability, being a reference in the institutional reception units of adolescents. Its performance has been essential in the non-formal education of the welcomed, sharing knowledge in the form of dialogue.